Correlation of Ultrasonic Pulse Velocity with Porosity and Compressive Strength of Mortar with Limestone for Building Quality Assessment - Slamet Widodo; Faqih Ma'arif; Maris Setyo Nugroho; Hidayat Mahardika (U Karst, 2022)
Mortar is used for bonding bricks, filling gaps in masonry, and as a plaster for strengthening and smoothing wall surfaces in finishing works. Poor quality of mortar can cause cracks in the walls which are identified after the building is completed. Assessment of a building is essential to determine its quality. Non-destructive testing is widely chosen because it will not directly affect the physical building condition. However, there still needs to achieve a good fit equation that can be used to estimate mortar quality using non-destructive testing. This research aimed to propose a formula to predict the mortar quality using an ultrasonic pulse velocity (UPV) test with porosity and compressive strength in the mortar with limestone. Variations in adding the lime powder to the mortar mix are 20%, 30%, 40%, and 55%. It was divided into M, S, N, and O types. The mortar cubes were prepared based on ASTM C-1329 and ASTM C-270. The specimens were then evaluated with UPV, porosity, and compressive strength test using three samples for each test. Equations for the relationship between UPV and porosity and compressive strength can be derived from these tests. The results showed that the value of the ultrasonic pulse speed is directly proportional to the compressive strength of the mortar, which fits the equation y = 0.0542e0.0015x, and is inversely proportional to the porosity, showing the equation y = 108.57e-6E-04x. The results of this study can be used to assess the quality of new construction works and existing buildings.